Living kidney donor evaluation for all candidates with normal estimated GFR for age. (20th May 2021) - Gaillard, François; Jacquemont, Lola; Lazareth, Hélène; Albano, Laetitia; Barrou, Benoit; Bouvier, Nicolas; Buchler, Mathias; Titeca‐Beauport, Dimitri; Couzi, Lionel; Delahousse, Michel; Ducloux, Didier; Etienne, Isabelle; et al.
Summary: Multiple days assessments are frequent for the evaluation of candidates to living kidney donation, combined with an early GFR estimation (eGFR). Living kidney donation is questionable when eGFR is <90 ml/min/1.73 m 2 (KDIGO guidelines) or 80 ml/min/1.73 m 2 (most US centres). However, age‐related GFR decline results in a lower eGFR for older candidates. That may limit the number of older kidney donors. Yet, continuing the screening with a GFR measure increases the number of eligible donors. We hypothesized that in‐depth screening should be proposed to all candidates with a normal eGFR for age. We compared the evolution of eGFR after donation between three groups of predonation eGFR: normal for age ( S age ) higher than 90 or 80 ml/min/1.73 m 2 ( S 90 and S 80, respectively); across three age groups (<45, 45–55, >55 years) in a population of 1825 French living kidney donors with a median follow‐up of 5.9 years. In donors younger than 45, postdonation eGFR, absolute‐ and relative‐eGFR variation were not different between the three groups. For older donors, postdonation eGFR was higher in S 90 than in S 80 or S age but other comparators were identical. Postdonation eGFR slope was comparable between all groups. Our results are in favour of in‐depth screening for all candidates to donation with a normal eGFR for age.